CdS nanosheets decorated with Ni@graphene core-shell cocatalyst for superior photocatalytic H2 production. (1st November 2020) - Di, Tingmin; Zhang, Liuyang; Cheng, Bei; Yu, Jiaguo; Fan, Jiajie
Abstract: A novel cocatalyst, i.e. metallic nickel nanoparticles encapsulated in few-layer graphene (Ni@C), is obtained by carbonization of metal–organic frameworks (MOF) and leaching treatment of hydrochloric acid. It is selected as the cocatalyst for CdS nanosheets, forming CdS-Ni@C nanocomposites. It remarkably improves the photocatalytic activities of CdS nanosheets due to the synergistic effect of Ni nanoparticles and graphene layers. In addition, the Ni nanoparticles encapsulated by graphene layers effectively isolate Ni from the ambient, which avoids contamination and curbs corrosion. The larger work function of Ni@C and outstanding conductivity of graphene promote the electron transfer from CdS to Ni@C, suppressing the recombination of photogenerated carriers and facilitating the separation of photogenerated electron-hole pairs. This strategy by adopting this novel cocatalyst provides a new solution to the improvement of the photocatalytic hydrogen production.